Cultural Brew: Designing Coffee-Based Tourism Packages to Boost Local MSMEs in Labuan Bajo - Ramadhan, Dicky Satria; Firdaus, Anzar Alfat; Munawaroh, Asyifa Nur Laely; Ramadhan, Eka Setya (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Labuan Bajo, designated as a super-priority tourism destination in Indonesia, possesses substantial potential for the development of culture-based tourism and the promotion of local products, particularly Manggarai coffee, which is deeply rooted in local traditions. Despite this potential, coffee-based products and experiences have not yet been systematically integrated into tourism offerings, highlighting the need for structured community service initiatives to strengthen coffee micro, small, and medium enterprises (MSMEs). This program was implemented through two main stages: identification and planning. The identification stage involved field observations and Focus Group Discussions (FGDs) with coffee MSME actors, local government representatives, travel agents, and community members to map opportunities and challenges in developing coffee-based tourism. The planning stage focused on designing an integrated coffee tourism package, comprising a Coffee Plantation Tour Plan as an educational and cultural tourism experience that introduces visitors to coffee cultivation processes and Manggarai cultural values, as well as a Coffee Souvenir Shopping Plan to position local coffee as a flagship regional product. The results indicate that these planned concepts have the potential to enhance Labuan Bajo’s tourism attractiveness, increase the economic value of local coffee MSMEs, and reinforce local cultural identity. This community service activity has produced an initial design that can serve as a foundation for the development of coffee-based tourism, contributing to inclusive and sustainable local economic growth. Furthermore, future development should advance toward pilot implementation and impact evaluation, supported by strengthened stakeholder partnerships, capacity building, and digital tourism integration to improve market reach and global competitiveness.